Telemedicine in Internal Medicine: A Review of Patient Outcomes, Physician Workload, and Healthcare System Efficiency - Benly Levi Andreas Sibarani; Maeike Grestiana Sinaga; Kartini Ganne Margareth; Aurora Fajria Anwari; Shella Sharon (International Journal of Health and Medicine, 2025)
In recent years, rapid advancements in digital technology have significantly transformed global healthcare delivery. The COVID-19 pandemic acted as a catalyst, accelerating the integration of information technology into healthcare systems, particularly through the increased adoption of telemedicine. In the field of internal medicine, which often involves long-term care and management of chronic illnesses, telemedicine presents a promising solution to enhance service accessibility, improve care efficiency, and sustain favorable clinical outcomes. This study aims to conduct a narrative review to explore the impact of telemedicine on patient clinical outcomes, healthcare worker workload, and healthcare system efficiency within internal medicine practice. The review is based on an analysis of peer-reviewed literature published between 2020 and 2025, sourced from major databases including PubMed, Scopus, and Web of Science. Article selection was based on relevance to the topics of telemedicine and internal medicine, contextual applicability, and full-text availability. The findings of the review reveal that telemedicine contributes positively by expanding access to care, reducing travel time and logistical barriers for patients, accelerating clinical response times, and decreasing patient congestion in healthcare facilities. These outcomes are particularly beneficial for patients with chronic conditions who require regular monitoring and consistent communication with healthcare providers. However, the implementation of telemedicine also introduces new challenges, including increased administrative responsibilities and digital workload for healthcare professionals. The study underscores the importance of equipping healthcare systems with adequate digital infrastructure, implementing supportive and flexible policies, and providing comprehensive training for healthcare workers. These measures are crucial to ensure the successful and sustainable adoption of telemedicine in internal medicine. Overall, telemedicine holds strong potential to reshape the future of internal medicine, provided that its integration is strategically managed to balance technological advancement with human-centered care.